Pengaruh Koordinasi Terhadap Efektivitas Kerja di Dinas Pangan dan Pertanian Kota Cimahi - Purnama, Indra; Rosadi, Barkah; Istikomah, Istikomah (Universitas Batanghari Jambi, 2024)
In an organization, good coordination is needed with regard to the abilities and expertise of employees, so that by itself the employee's duties can be carried out properly with full responsibility. That way it will create job satisfaction and give effect to the work effectiveness of each employee. One of the most important organizational components is coordination and work effectiveness. In an effort to achieve work effectiveness, the Food and Agriculture Office of the City of Cimahi has tried various efforts which basically cover four management functions, namely planning, organizing, implementing and supervising. The four management functions are carried out by the Food and Agriculture Service of Cimahi City with the aim of integrating the efforts of each individual and work unit within the Service in order to achieve the expected goals. The research objective was to find out the effect of coordination on work effectiveness in the Food and Agriculture Service of Cimahi City. Quantitative research methods were used in this study where employees of the Cimahi City Food and Agriculture Service became the population with a sample of 78 people. The technique used is simple linear regression analysis. The results obtained in this study were obtained by analysis of the coefficient of determination test known that the R-Square coefficient value was 0.836 or 83.6%, so it can be concluded that the effect of the independent variable, namely coordination on work effectiveness in the Food and Agriculture Service of Cimahi City, was 0.836 or 83.6% . In addition, the remaining 16.4% was influenced by other factors that were not present in this study.